Differences in genome, transcriptome, miRNAome, and methylome in synchronous and metachronous liver metastasis of colorectal cancer - Horak, Josef; Kubecek, Ondrej; Siskova, Anna; Honkova, Katerina; Chvojkova, Irena; Krupova, Marketa; Manethova, Monika; Vodenkova, Sona; García-Mulero, Sandra; John, Stanislav; Cecka, Filip; Vodickova, Ludmila; et al. (Frontiers in Oncology, 2023)
Despite distant metastases being the critical factor affecting patients' survival, they remain poorly understood. Our study thus aimed to molecularly characterize colorectal cancer liver metastases (CRCLMs) and explore whether molecular profiles differ between Synchronous (SmCRC) and Metachronous (MmCRC) colorectal cancer. This characterization was performed by whole exome sequencing, whole transcriptome, whole methylome, and miRNAome. The most frequent somatic mutations were in APC, SYNE1, TP53, and TTN genes. Among the differently methylated and expressed genes were those involved in cell adhesion, extracellular matrix organization and degradation, neuroactive ligand-receptor interaction. The top up-regulated microRNAs were hsa-miR-135b-3p and -5p, and the hsa-miR-200-family while the hsa-miR-548-family belonged to the top down-regulated. MmCRC patients evinced higher tumor mutational burden, a wider median of duplications and deletions, and a heterogeneous mutational signature than SmCRC. Regarding chronicity, a significant down-regulation of SMOC2 and PPP1R9A genes in SmCRC compared to MmCRC was observed. Two miRNAs were deregulated between SmCRC and MmCRC, hsa-miR-625-3p and has-miR-1269-3p. The combined data identified the IPO5 gene. Regardless of miRNA expression levels, the combined analysis resulted in 107 deregulated genes related to relaxin, estrogen, PI3K-Akt, WNT signaling pathways, and intracellular second messenger signaling. The intersection between our and validation sets confirmed the validity of our results. We have identified genes and pathways that may be considered as actionable targets in CRCLMs. Our data also provide a valuable resource for understanding molecular distinctions between SmCRC and MmCRC. They have the potential to enhance the diagnosis, prognostication, and management of CRCLMs by a molecularly targeted approach.